Comparison of the Effectiveness of Parent-Centered Play Therapy and Child-Centered Play Therapy on Social Adjustment among Students with Social Anxiety Disorder - Amiri Doomari , Elahe; Heydari, Shaban; Salim Bahrami, Seyedeh Hamideh (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to compare the effectiveness of parent-centered play therapy and child-centered play therapy on the social adjustment of elementary school students diagnosed with Social Anxiety Disorder. Methods and Materials: This study employed a quasi-experimental design with a pretest–posttest and follow-up structure involving two experimental groups and one control group. The statistical population consisted of all male and female elementary school students with Social Anxiety Disorder in Zahedan, Iran, during the 2024–2025 academic year. Sixty students aged 7 to 8 years who met the inclusion criteria were selected through convenience sampling and randomly assigned to a parent-centered play therapy group (n = 20), a child-centered play therapy group (n = 20), and a control group (n = 20). Participants were identified using the Social Anxiety Questionnaire and clinical diagnostic criteria. Data were collected using the Children’s Social Adjustment Questionnaire. The parent-centered play therapy intervention was implemented according to the Child–Parent Relationship Therapy model in ten weekly sessions, whereas the child-centered play therapy intervention consisted of sixteen sessions delivered over eight weeks. Data were analyzed using repeated-measures analysis of variance and Bonferroni post hoc tests. Findings: The results of repeated-measures analysis of variance revealed a significant effect of time on social adjustment, F = 485.049, p < .001, η² = .895, indicating significant changes across pretest, posttest, and follow-up assessments. A significant Time × Group interaction effect was also observed, F = 65.901, p < .001, η² = .698, demonstrating differential patterns of change among the three groups. Furthermore, the between-group effect was statistically significant, F = 69.668, p < .001, η² = .710, indicating meaningful differences in social adjustment among the intervention and control groups. Bonferroni post hoc comparisons showed that both parent-centered play therapy and child-centered play therapy significantly improved social adjustment compared with the control group (p < .001). In addition, a significant difference was found between the two intervention groups (p < .001), indicating that parent-centered play therapy produced greater improvements in social adjustment than child-centered play therapy. Conclusion: The findings indicate that both parent-centered and child-centered play therapy are effective interventions for enhancing social adjustment among children with Social Anxiety Disorder.